Fine-Tuning Tumor Endothelial Cells to Selectively Kill Cancer - Uldry, Emilie (Int J Mol Sci, 2017)
Tumor endothelial cells regulate several aspects of tumor biology, from delivering oxygen and nutrients to shaping the immune response against a tumor and providing a barrier against tumor cell dissemination. Accordingly, targeting tumor endothelial cells represents an important modality in cancer therapy. Whereas initial anti-angiogenic treatments focused mainly on blocking the formation of new blood vessels in cancer, emerging strategies are specifically influencing certain aspects of tumor endothelial cells. For instance, efforts are generated to normalize tumor blood vessels in order to improve tumor perfusion and ameliorate the outcome of chemo-, radio-, and immunotherapy. In addition, treatment options that enhance the properties of tumor blood vessels that support a host’s anti-tumor immune response are being explored. Hence, upcoming anti-angiogenic strategies will shape some specific aspects of the tumor blood vessels that are no longer limited to abrogating angiogenesis. In this review, we enumerate approaches that target tumor endothelial cells to provide anti-cancer benefits and discuss their therapeutic potential.